Analisis Efektivitas Pemberian Insentif Pajak Penghasilan Pasal 21 Ditanggung Pemerintah Pada Masa Pandemic Covid-19 (Studi Kasus KPP Madya Bekasi Tahun 2020 - 2021) - Fidiyah Nurhasanah; Mainita Hidayati (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
The phenomenon in this study is the devastation of the covid-19 pandemic that has hit the whole world, including Indonesia, which has made a decline in the economic activity and productivity of business actors. Therefore the government was trying to provide stimulation fromthe tax sector in the form of providing incentives for Income Tax Article 21 borne by the government, the aim was to ease the tax burden so that business actors, especially employees, can maintain purchasing power during the difficult times of the covid-19 pandemic. The purpose of this study was to analyze the effectiveness of providing income tax article 21 incentives borne by the government. This study used a qualitative approach with a descriptive method. data collection techniques used the method of observation, interviews, and documentation. The results of this study showed the effectiveness in terms of taxpayers who take advantage of the Article 21 Income Tax incentives borne by the government in 2020 by 94% and in 2021 by 99%. As for the indicators of effectiveness, i.e.: 1) aspects of achieving goals are on target and running according to goals, 2) aspects of integration in terms of socialization are still not optimal because there are taxpayers who make mistakes in submitting reports on the realization, this is of course, because of lack of socialization in how to do it correctly, in terms of procedures, it is effective because it can be submitted online, 3) aspects of adaptation in terms of procurement of facilities & infrastructure do not use a special room because it is done online, in terms of human resources it is quite good because the employees are very knowledgable and informative.